Mobile Applications in Otology: A Scoping Review - Valdez, Laurence Troy S.; Cafino, Rentor Y.; Isla Jr., Armando T.; Ignacio, Eigen John T.; Labra, Patrick John; Velasco, Lemuel Clark P. (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This scoping review aims to comprehensively synthesize current research on the use of mobile applications in otology, identify research gaps, and assess the feasibility of mobilebased applications in this field. The aim is to support and direct future research studies on harnessing the potential of mobile technology in otology. Following the PRISMA-ScR guidelines, a literature profiling approach was adopted using the Google Scholar search engine from September 2022 to January 2023. Only articles published in English between 2012 and 2023 were included, resulting in a final sample size of 32 papers. The results revealed an increasing focus on the remote delivery of healthcare, with the majority of the articles originating from the United States and authored by medical doctors. Two main categories were identified within the 32 selected journals: audiology and smartphone otoscopy. A total of 124 mobile applications were identified in these journals, with 48 applications for hearing tests and 27 applications for smartphone otoscopes being the most commonly utilized. Mobile applications have the potential to serve as valuable tools in the field of otology, especially in the context of smartphone hearing tests and smartphone-enabled otoscopes. However, further research is needed to assess their effectiveness, accuracy, and appropriate usage.